2009
DOI: 10.1136/bmj.b4914
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of attitudes to ageing in the Economist: apocalyptic demography for opinion formers

Abstract: This negative view of older people might be influential in shaping the attitudes of readers, who include opinion formers in political and economic circles. Gerontologists (including geriatricians) need to engage with influential media, as well as helping to promote a professional development of journalists that is informed and knowledgeable about the negative impact of ageism on the wellbeing of older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 19 publications
2
54
1
2
Order By: Relevance
“…11 Or should we indulge in 'apocalyptic demography'? 12 Some social scientists argue that it is demographic change that has a profound impact on the social, economic and political trends of a country rather than cause and effect operating the other way round. Summary Planning for the future development of mental health services requires an understanding of the changing demographics of local populations.…”
Section: The Challengementioning
confidence: 99%
See 1 more Smart Citation
“…11 Or should we indulge in 'apocalyptic demography'? 12 Some social scientists argue that it is demographic change that has a profound impact on the social, economic and political trends of a country rather than cause and effect operating the other way round. Summary Planning for the future development of mental health services requires an understanding of the changing demographics of local populations.…”
Section: The Challengementioning
confidence: 99%
“…It is this secular theory that appears to have captured media interest and concern. 12 We cannot risk simply pinning our hopes on morbidity compression. The potential changes of most relevance to mental health services if it is 'chronic pandemy' that emerges include more people with dementia, 14 comorbid chronic physical illness and mental health problems 15 and depression.…”
Section: Moira Connollymentioning
confidence: 99%
“…Den utvecklade världens befolkning åldras och den vårdsituation som detta ger upphov till liknas ibland vid en tidsinställd bomb (Martin, Williams & O'Neill 2009). I länder som Spanien, Italien, Japan och USA går det snart två personer i gruppen 65 år och äldre på varje person i gruppen 20 år och yngre, och den högsta levnadsåldern förskjuts ständigt uppåt.…”
Section: Inledningunclassified
“…As Nordenfelt ([58] p. 75) stated "this must be a dignity attached to the person's integrity and identity as a human being". As the participants in this study revealed, older patients who wish to die are often referred to as being "tired of living" [59].…”
Section: A L Holm Et Al Open Journal Of Nursingmentioning
confidence: 99%